Kids+ Parent Infant Program (PIP): a community model for supporting partnerships in early developmental follow-up and support - Reynolds, K.; Urbanowicz, A.; Mayston, M.; Foley, S. (Frontiers in Pediatrics, 2024)
High-risk infants are discharged home from hospital with increased care needs and the potential for the emergence of developmental disabilities, contributing to high levels of parental stress and anxiety. To enable optimal outcomes for high-risk infants and their families, developmental followup programs need to continue following hospital discharge. However, current follow-up care for high-risk infants is variable in terms of type, access and equity, and there seems to be a gap in existing services such as supporting the transition home, parental support, and inclusion of all at-risk infants regardless of causality. Routine follow-up that identifies developmental delays or neuromotor concerns can facilitate timely referral and access to targeted intervention during critical periods of development. The Kids+ Parent Infant Program (PIP) is a unique model of developmental follow-up that shares some characteristics with established programs, but also includes additional key elements for a seamless, wrap-around service for all high-risk infants and their families living in a regional area of Australia. This community-based program provides integrated assessment and intervention of infants, alongside parent support and education, embracing a holistic model that accounts for the complexity and interrelatedness of infant, parent, medical and developmental factors. By prioritising the well-being of high-risk infants and their families, the Kids+ PIP paves the way for improved developmental outcomes and provides an innovative model for developmental follow-up, with the potential for reproduction in other healthcare settings.